Empirical evidence-based policy for Islamic psycho-spiritual intervention: using electroencephalography for post-traumatic stress disorder - Hassan, Siti Aishah; Zakaria, Noor Syamilah; Ahmad, Nor Aniza (Human Resource Management Academic Research Society, 2017)
Providing empirical evidence in an experimental study with randomized control trials design has been considered as a gold standard among the scientific community. Islamic psycho-spiritual study is currently categorized as pseudo-science; hence deserve a more scientific approach to substantiate its proposition. Despite clinical psychology is considered as more scientific, studies indicate that post-traumatic stress disorder (PTSD) has often been misdiagnosed and thus the treatment may not be effective. Therefore, we proposed a more scientific instrument using Electroencephalography (EEG) to measure the effectiveness of Islamic Psycho -spiritual Intervention (IP-SI) among PTSD subjects who were victims of the massive flood 2014/2015 in Malaysia. Objective: This study aims to suggest an empirical evidence-based policy on the effectiveness of the Islamic Psycho-spiritual intervention. The general objective of this study is to test the effect of the Islamic Psycho-spiritual intervention on PTSD subjects who were victims of the massive flood. Method: The gold standard method of randomized controlled trials design was adopted in this experimental study. Sample (n =73) were selected from two different location of transits houses in Kampung Tualang, Kuala Krai, Kelantan, randomly assigned to experimental and control groups. The experimental group received psycho-spiritual treatment of group psycho-education and listening to surah Yasin while wearing EEG cap. The control group did not listen to surah Yasin while wearing the EEG cap. Data were collected using Mindo wireless 32-channels EEG. PTSD was assessed using instrument parallel to Diagnostic Statistical Manual (DSM-5). The collected data was analysed with t-test to examine the significant difference in EEG signals between pre and post of experimental group and control group. Result: The findings indicated there were significant differences in EEG signals with medium effect sizes between pre and post-treatment times for experimental group, t (35) = 3.43, p =.002, and between control and experiment groups at post treatment time , t (35) =2.569, p=.009. Thus, the findings provide an empirical evidence to support for the effectiveness of IP-SI. Accordingly, policies for empirical evidence-based Islamic psycho-spiritual intervention are recommended for the government and the related agency.